2015
DOI: 10.1016/j.palaeo.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

δ13Corg and n-alkane evidence for changing wetland conditions during a stable mid-late Holocene climate in the central Tibetan Plateau

Abstract: δ 13 C org and n-alkane evidence for changing wetland conditions during a stable mid-late Holocene climate in the central Tibetan Plateau, Palaeogeography, Palaeoclimatology, Palaeoecology (2015), doi: 10.1016/j.palaeo.2015 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…is dominated by n-C 29 . Those findings are in line with previous regional studies, which report n-C 31 being mainly produced by grasses/herbs and n-C 29 by deciduous trees and shrubs (Cheung et al, 2015;Wang et al, 2018c;Liu et al, 2018;Bliedtner et al, 2018a). Although Artemisia spp.…”
Section: N-alkane Pattern In Plantssupporting
confidence: 93%
“…is dominated by n-C 29 . Those findings are in line with previous regional studies, which report n-C 31 being mainly produced by grasses/herbs and n-C 29 by deciduous trees and shrubs (Cheung et al, 2015;Wang et al, 2018c;Liu et al, 2018;Bliedtner et al, 2018a). Although Artemisia spp.…”
Section: N-alkane Pattern In Plantssupporting
confidence: 93%
“…Semi-arid and arid Mongolia is a highly continental region characterised by harsh and long winters and hot and short summers (Dashkhuu et al, 2015). Mongolia is located at the interface of three major atmospheric circulation systems controlling the regional climate (Fig.…”
Section: Geographical Setting and Samplingmentioning
confidence: 99%
“…The δ 13 C of Kobresia meadows (mainly Cyperaceae) was measured to c . −13‰ (Cheung et al ., ). In addition, high δ 13 C values in Lake Wuxu sediments appeared synchronously with higher herbaceous pollen components especially species from Cyperaceae, Poaceae and Chenopodiaceae between 6.0 and 4.2 cal ka bp , indicating high supplies of terrestrial organic materials, especially fragments of C 4 land plants (Zhang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Leaf wax carbon isotope ratios from Lake Qinghai indicated that C 4 plants accounted for 50% of the terrestrial primary productivity on the north-eastern Tibetan Plateau throughout the Lateglacial and early Holocene (Thomas, et al, 2014). The δ 13 C of Kobresia meadows (mainly Cyperaceae) was measured to c. −13‰ (Cheung et al, 2015). In addition, high δ 13 C values in Lake Wuxu sediments appeared synchronously with higher herbaceous pollen components especially species from Cyperaceae, Poaceae and Chenopodiaceae between 6.0 and 4.2 cal ka BP, indicating high supplies of terrestrial organic materials, especially fragments of C 4 land plants (Zhang et al, 2016).…”
Section: Source Of Organic Materialsmentioning
confidence: 99%
See 1 more Smart Citation